In vitro Metabolism of Grandisin, a Lignan with Anti-chagasic Activity - De Santis Ferreira, Leandro; Callejon, Daniel Roberto; Engemann, Anna; Cramer, Benedikt; Humpf, Hans-Ulrich; de Barros, Valéria Priscila; Assis, Marilda das Dores; da Silva, Denise Brentan; de Albuquerque, Sérgio; Okano, Laura Tiemi; Kato, Massuo Jorge; Lopes, Norberto Peporine (Planta Medica, 2012)
Tetrahydrofuran lignans represent a well-known group of phenolic compounds capable of acting as antiparasitic agents. In the search for new medicines for the treatment of Chagas disease, one promising compound is grandisin which has shown significant activity on trypomastigote forms of Trypanosoma cruzi. In this work, the in vitro metabolism of grandisin was studied in the pig cecum model and by biomimetic phase I reactions, aiming at an ensuing a preclinical pharmacokinetic investigation. Although grandisin exhibited no metabolization by the pig microbiota, one putative metabolite was formed in a biomimetic model using Jacobsen catalyst. The putative metabolite was tested against T. cruzi revealing loss of activity in comparison to grandisin.
Keywords: tetrahydrofuran lignans; grandisin; in vitro metabolism; Piper solmsianum; Piperaceae; Jacobsen catalyst